A comparison of 30-day complications following plate fixation versus intramedullary nailing of closed extra-articular tibia fractures. Issue 4 (April 2015) - Minhas, Shobhit V.; Ho, Bryant S.; Switaj, Paul J.; Ochenjele, George; Kadakia, Anish R.
Abstract: Background and purpose: Tibial shaft fractures are often treated by intramedullary nailing (IMN) or plate fixation. Our purpose was to compare the 30-day complication rates between IMN and plate fixation of extra-articular tibial fractures. Materials and methods: We conducted a retrospective analysis of prospectively collected patient demographics, comorbidities, and 30 day complications of isolated closed extra-articular tibial shaft fractures from 2006 to 2012 using the American College of Surgeon's National Surgical Quality Improvement Program (ACS-NSQIP) database. A 1:2 propensity-matched dataset was created to control for differences in preoperative demographics and comorbidities across the plate fixation and IMN groups. Univariate and multivariate analyses were used to assess differences in complications between the groups and the independent effects of plate fixation or IMN on complications. Results: A total of 771 patients were identified with 234 (30.4%) in the plate fixation and 537 (69.6%) in the IMN group. We found no statistical difference in rates of wound complications, medical complications, reoperation, or mortality in our propensity matched analyses. Plate fixation was found to be independently associated with a lower risk of postoperative blood transfusion compared to IMN (odds ratio 0.326, p = 0.032). Plate fixation was not independently associated with any other examined complications. Conclusions: We found no difference in 30-day postoperative complications between plate fixation and intramedullary nailing of isolated extra-articular tibia fractures with the exception of decreased postoperative transfusion requirements with plate fixation. We conclude that both procedures offer a similar short-term complication profile.